1996
DOI: 10.1103/physrevb.53.6129
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved optical studies ofF-center diffusion in KBr crystals

Abstract: Spatially resolved optical studies of F-center diffusion during and after the photothermal F→X color center conversion have been performed by optical scanning and holographic methods in electrolytically colored KBr crystals. Average velocities and diffusion coefficients of F centers have been determined for Gaussian and periodical spatial exposing light intensity distributions. A strong influence of the light intensity gradient has been found on F-center diffusion. It manifests itself by a rapid increase of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…We used the lowest reported value of the barrier realizing for photo excited F‐centers ( F *‐centers) in alkali halides (0.2 eV in KCl, KBr) for an estimation. This barrier is comparable to the diffusion barrier of H‐ and I‐centers 33, 34. We obtained that, due to a very short life‐time of the transient ionized state of the lattice (10 −14 –10 −11 s), even for this extremely low diffusion barrier the diffusion lengths of F‐centers is too short to describe the observed difference between the radial distributions of valence holes and F‐centers detected in a track.…”
Section: Resultsmentioning
confidence: 77%
“…We used the lowest reported value of the barrier realizing for photo excited F‐centers ( F *‐centers) in alkali halides (0.2 eV in KCl, KBr) for an estimation. This barrier is comparable to the diffusion barrier of H‐ and I‐centers 33, 34. We obtained that, due to a very short life‐time of the transient ionized state of the lattice (10 −14 –10 −11 s), even for this extremely low diffusion barrier the diffusion lengths of F‐centers is too short to describe the observed difference between the radial distributions of valence holes and F‐centers detected in a track.…”
Section: Resultsmentioning
confidence: 77%
“…6(a)). The H-centers are highly mobile in the crystal, even at room temperature, whereas F-centers are immobile in their ground state, but mobile in their excited state (F * -centers) [55]. The F-centers can be excited either by the primary electrons or by co-excitation with visible light within the F-center absorption band [56].…”
Section: Electronsmentioning
confidence: 99%
“…It has been found previously that the ground state F centers are immobile, whereas excited and relaxed F ‫ء‬ centers can easily diffuse in the crystal [13][14][15]. In the recent paper Salminen et al [15] have demonstrated that initially uniform F center concentration in electrolytically colored KBr crystal can be modulated, if the crystal is exposed to 518 nm light which is within the F-center absorption band.…”
mentioning
confidence: 96%
“…In the recent paper Salminen et al [15] have demonstrated that initially uniform F center concentration in electrolytically colored KBr crystal can be modulated, if the crystal is exposed to 518 nm light which is within the F-center absorption band. The light induces the F-center diffusion and aggregation.…”
mentioning
confidence: 98%
See 1 more Smart Citation